Characteristics of Frequent Dynamic Triggering of Microearthquakes in Southern California. Issue 1 (20th January 2021) - Fan, Wenyuan; Barbour, Andrew J.; Cochran, Elizabeth S.; Lin, Guoqing
Abstract: Dynamic triggering of earthquakes has been reported at various fault systems. The triggered earthquakes are thought to be caused either directly by dynamic stress changes due to the passing seismic waves, or indirectly by other nonlinear processes that are initiated by the passing waves. Distinguishing these physical mechanisms is difficult because of the general lack of high‐resolution earthquake catalogs and robust means to quantitatively evaluate triggering responses, particularly, delayed responses. Here we use the high‐resolution Quake Template Matching catalog in Southern California to systematically evaluate teleseismic dynamic triggering patterns in the San Jacinto Fault Zone and the Salton Sea Geothermal Field from 2008 to 2017. We develop a new statistical approach to identify triggered cases, finding that approximately 1 out of every 5 global M w  ≥ 6 earthquakes dynamically trigger microearthquakes in Southern California. The triggering responses include both instantaneous and delayed triggering, showing a highly heterogeneous pattern and indicating possible evolving triggering thresholds. We do not observe a clear peak ground velocity triggering threshold that can differentiate triggering earthquakes from nontriggering events, but there are subtle differences in the frequency content of the ground motion that may differentiate the earthquakes. In contrast to the depth distribution of background seismicity, the identified triggered earthquakes tend to concentrate at the edges of the seismogenic zones. Although instantaneously triggered earthquakes are likely a result of dynamic Coulomb stress changes, the cases of delayed‐dynamic triggering are best explained by nonlinear triggering processes, including cyclic material fatigue, accelerated transient creep, and stochastic frictional heterogeneities. Plain Language Summary: Earthquake‐to‐earthquake interaction and triggering are frequently observed at various fault systems. For example, large earthquakes can cause aftershocks in the near‐field region by permanently altering the stress field, which is termed static earthquake triggering. Seismic waves from earthquakes can also trigger events on faults up to thousands of kilometers away. Such triggering processes are called dynamic triggering. At such great separation distances, the stress perturbation of dynamic triggering is commonly small, which is perplexing from a physical perspective. With a high‐resolution earthquake catalog in Southern California, our study shows that local earthquakes are frequently triggered by remote earthquakes. The majority of these local earthquakes are triggered with a delayed response, sometimes occurring hours after the seismic wave passage. Our results suggest that seismic waves cause temporary disturbances in the underlying physical responses within the subsurface, with triggering thresholds that can change in both space and time. Key Points: Distant earthquakes frequently trigger local microearthquakes in Southern California Both instantaneous and delayed‐dynamic triggering occur in the region Nonlinear triggering processes likely dominate the observed cases